Genome-wide association study on cerebral white-matter hyperintensities in 36, 577 individuals. (3rd October 2022) - Jespersen, J; Ahlberg, G; Andreasen, L; Ghouse, J; Frederiksen, K S; Haunsoe, S; Svendsen, J H; Frikke-Schmidt, R; Olesen, M S; Bundgaard, H
Abstract: Background/Introduction: A quarter of all strokes are caused by cerebral small vessel disease (CSVD), which is also the most common pathology underlying vascular dementia. [1] White matter hyperintensities (WMH), a radiological marker detectable on magnetic resonance imaging (MRI), can serve as a proxy for CSVD. WMH is associated with stroke, increased risk of dementia and functional decline in older age. [2, 3] Purpose: We aimed at investigating the genetic architecture of WMH using cerebral MRI data. Methods: We used imaging data ∼40, 000 individuals from the UK Biobank, a large population-based, prospective cohort study. We selected individuals with available total volume of WMH from T1 and T2_FLAIR images. We performed a genome-wide association study (GWAS) on autosomal genetic variants assuming an additive model based on genotype dosages with BOLT-LMM treating WMH as outcome. We applied LD score regression (LDSC software) to estimate the genetic correlation between WMH traits and traits selected based on availability and relevance for cardiovascular disease. Results: We included a total of 36, 577 individuals with available quality controlled cerebral MRI data. Genome-wide analysis identified 20 loci of statistical significance, six of which are not previously reported (Fig. 1). Within these novel loci, the following genes are located in proximity to lead variants: EHBP1, OTX1, WDPCP, VCAN, WNT16, FAM3C, ERI1, PRAG1, CACNB2, MTHFSD, FOXL1, FOXC2. Using BOLT, we found the heritability of WMH to be 37%. We investigated genetic correlation between WMH and multiple phenotypes (Fig. 2). We observed the highest correlation with small vessel stroke (rg=0.56, P=3.9x10 –4 ) Interestingly, WMH was genetically correlated with left atrial volume (rg=0.24, P=2.8x10 –3 ). Conclusion: In a GWAS on WMH acquired from cerebral MRI, we identified 20 significant loci, of which six are novel. This genetic study provides insights on the biological understanding and epidemiology of CSVD. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): John and Birthe Meyer FoundationThe Hallas-Møller Emerging Investigator Novo Nordisk